Culture and mental disorders - Jak, Andrzej (Studia Psychologica: Theoria et praxis, 2003)
The main subject of the paper is the presentation of the relationship of mental health and mental disorders to culture from the point of view of contemporary psychiatry. In this review of the literature, the author reports on methods and basic concepts for comparative studies of mental illness in different cultural groups. The author distinguishes cultural psychiatry from transcultural and cross-cultural psychiatry. At the beginning, this work concerns definition of terms, history of the field, cultural relativism (behavior patterns that we regard as normal may be defined in other cultures as abnormal) and a map of the problems to be approached. Successively, the paper focuses predominantly on epidemiology, etiology, etiopathogenesis, and clinical types of mental disorders in different cultures. A very important topic is that of specific mental disorder syndromes (so-called exotic syndromes) determined by culture, e.g. koro, susto, thanatomania, pa-ling, latah, amok, witico, transient psychoses, possession, t nce etc. To problem the author devotes a good deal of attention. Finally, the author presents different methods of therapy, suggesting that the relative therapy is the best.